Stenting of symptomatic intracranial stenosis using balloon mounted coronary stents: a single center experience. (19th March 2014) - Durst, Christopher R; Geraghty, Scott R; Southerland, Andrew M; Starke, Robert M; Rembold, Karen; Malik, Shaneela; Wintermark, Max; Liu, Kenneth C; Crowley, R Webster; Gaughen, John; Jensen, Mary E; Evans, Avery J
Abstract : Objective: Intracranial atherosclerotic disease is the cause of up to 10% of ischemic strokes and transient ischemic attacks. Intracranial stenting with off-label balloon mounted coronary stents (BMCS) may be a viable alternative for patients with symptomatic intracranial stenosis who fail best medical therapy. Design: Between December 2005 and June 2012, 42 symptomatic intracranial stenoses were treated with a BMCS after failing medical management. Procedural records, clinical outcomes, and imaging follow-up were reviewed. Outcome measurements included technical success rate, morbidity and mortality, long term stent patency, and clinical outcomes, as measured by the modified Rankin Scale. Results: The technical success rate was 98% (41 of 42 lesions). Morbidity within the first 30 days was 7.1% (three of 42 lesions). Overall morbidity, including both periprocedural and long term evaluation, was 9.5% (four of 42 lesions). There were no deaths. Follow-up imaging was available for 30 stents (71%) with an average follow-up time of 35.1 months. Restenosis (>50%) and retreatment were observed in 20% and 10% of cases, respectively. Clinical evaluation by a neurologist ≥30 days postprocedure was available in 40 of 42 cases (95%) with an average of 32.1 months. At presentation, 55% of patients had a modified Rankin Scale (mRS) score of ≤2. At follow-up, 74% of patients were found to have an mRS score of ≤2. Conclusions: This study suggests that BMCS may benefit patients with symptomatic intracranial stenosis who experience stroke or transient ischemic attack in spite of best medical therapy.